2020
DOI: 10.1101/2020.12.18.423552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sterilizing immunity against SARS-CoV-2 in hamsters conferred by a novel recombinant subunit vaccine

Abstract: A safe and effective SARS-CoV-2 vaccine is essential to avert the on-going COVID-19 pandemic. Here, we developed a subunit vaccine, which is comprised of CHO-expressed spike ectodomain protein (StriFK) and nitrogen bisphosphonates-modified zinc-aluminum hybrid adjuvant (FH002C). This vaccine candidate rapidly elicited the robust humoral response, Th1/Th2 balanced helper CD4 T cell and CD8 T cell immune response in animal models. In mice, hamsters, and non-human primates, 2-shot and 3-shot immunization of StriF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The authors observed a weak humoral immune response to 10 μg of trimeric RBD in hamsters, while the titers of specific antibodies in immunized primates were high. When immunized with S-protein, the humoral immune response in both hamsters and primates was equally high [ 29 ]. One more example was published by Dalvey et al The authors obtained virus-like particles (VLPs) containing the engineered RBD variant with increased immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed a weak humoral immune response to 10 μg of trimeric RBD in hamsters, while the titers of specific antibodies in immunized primates were high. When immunized with S-protein, the humoral immune response in both hamsters and primates was equally high [ 29 ]. One more example was published by Dalvey et al The authors obtained virus-like particles (VLPs) containing the engineered RBD variant with increased immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there are no publications that use hamster models to study RBD-based vaccines. The only exception is the preprint by Wu et al, in which the authors observed a weak humoral immune response to RBD in immunized hamsters [ 29 ]. This case and the disturbing lack of hamsters in RBD-based subunit vaccine studies suggests that the predictive value of this animal model may be weak, specifically for vaccines that induce antibodies against RBD.…”
Section: Introductionmentioning
confidence: 99%